The Silk Road a new history with documents - Hansen, Valerie 1958- (Oxford University Press, 2017)
"The Silk Road. We have a hazy mental image: a lone traveler carrying silk on a camel moves along a desert. Where exactly is he going and what goods is he carrying? This book offers concrete answers based on newly discovered documents preserved in the sands of the Taklamakan Desert. It is amazing what has been dug up, and how the new materials...both documents and artifacts...radically challenge our understanding of the Silk Road. Historians have only recently begun to piece together and make sense of these materials, which give a far clearer picture of actual Silk Road. Placing these documentary finds at the heart of the narrative, this book also tells the story of the different explorers who found these documents, and it teases out the implications of these documents for our understanding of the Silk Road (we learn, for example, that the Silk 'Road' was not really a road, and that no one used the term 'Silk Road' in the past.) The book focuses on the seven most important Silk Road sites that have produced document and objects from the Silk Road. Six (Niya, Kucha, Turfan, Dunhuang, Khotan, and Xi'an) are located in northwest China; the seventh, Samarkand, is in modern Uzbekistan. This college edition includes a selection of excerpted primary sources in each chapter. The range is enormous: memoirs of medieval Chinese monks and modern explorers, letters written by women, descriptions of towns, language-learning materials for traveling monks, and contracts, among others. Instructors can select the documents they find most interesting to discuss in class; students can use these materials write papers. Many of these are difficult to find, and the author has checked all the translations to enhance their readability"...Provided by publisher
Keywords: Geschichte; Historic sites -- Silk Road; Trade routes -- Asia -- History; Asien; Silk Road -- History; Silk Road -- History -- Sources; Silk Road -- History, Local; Silk Road -- Description and travel; Seidenstraße; Quelle